2009
DOI: 10.1002/hipo.20631
|View full text |Cite
|
Sign up to set email alerts
|

Exercise enhances hippocampal‐dependent learning in the rat: Evidence for a BDNF‐related mechanism

Abstract: Short periods of forced exercise have been reported to selectively induce enhancements in hippocampal-dependent cognitive function, possibly via brain-derived neurotrophic factor (BDNF)-mediated mechanisms. In this study, we report that 1 week of treadmill running significantly enhanced both object displacement (spatial) and object substitution (nonspatial) learning. These behavioral changes were accompanied by increased expression of BDNF protein in the dentate gyrus, hippocampus, and perirhinal cortex. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 34 publications
12
114
1
2
Order By: Relevance
“…The results presented here demonstrate that one week of forced moderate exercise can improve spatial memory, as assessed using the object displacement task, in young, healthy adult rats, in agreement with previous findings in our laboratory [16]. Other reports in the literature suggest that in order for short-term exercise to enhance spatial learning, a deficit (insult, lesion, stress, ageing) must be present [16,[25][26][27].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results presented here demonstrate that one week of forced moderate exercise can improve spatial memory, as assessed using the object displacement task, in young, healthy adult rats, in agreement with previous findings in our laboratory [16]. Other reports in the literature suggest that in order for short-term exercise to enhance spatial learning, a deficit (insult, lesion, stress, ageing) must be present [16,[25][26][27].…”
Section: Discussionsupporting
confidence: 92%
“…We have suggested that this increase in BDNF (and the subsequent stimulation of downstream signalling pathways) is directly responsible for the improvements observed in spatial and object recognition learning, via a mechanism that is distinct from that of environmental enrichment [17]. We have also shown that the intracerebroventricular administration of a physiological dose of exogenous BDNF is sufficient to mimic the improvement in object recognition learning induced by this exercise paradigm [16]. Here, we have extended this previous work to analyse the intracellular signalling mechanisms that may underlie the observed exercise-induced and BDNF-induced cognitive improvements.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…These findings suggest that the hippocampus may have a role in this type of spatial learning. This form of learning appears to require expression of neurotrophins (Calamandrei et al, 2002;Niewiadomska et al, 2006) and exercise-induced enhancement of task performance has been associated with increases in hippocampal and perirhinal BDNF (Griffin et al, 2009). Furthermore, successful performance of the task is dependent on glutamatergic signalling through NMDA (Roullet et al, 1996;Usiello et al, 1998;Larkin et al, 2008) and AMPA receptors (Roullet et al, 2001).…”
Section: The Role Of the Perirhinal Cortex In Context And Spatial Memorymentioning
confidence: 99%